Jesus as Scapegoat in Matthew’s Roman-Abuse Scene (Matt 27:27–31) - Moscicke, Hans (Novum Testamentum, 2020)
Behind the cruel mockery of Pilate’s auxiliary troops (Matt 27:27-31), Matthew portrays the royal inauguration of the true cosmic lord. But what has often been missed is that this inauguration also entails Jesus’s cultic elimination as the victim in a performance reminiscent of ancient curse-transmission rituals. Matthew transforms and assimilates the scene to the most famous elimination rite in his Jewish context, the Yom Kippur scapegoat ritual. Jesus becomes a king who himself bears and carries away the moral impurities of the denizens of his own kingdom as the typological fulfillment of the scapegoat of Leviticus 16.